MEMBRANES SWEEPING AND ITS EFFECT ON DURATION OF PREGNANCY IN LOW-RISK CASES - Malik, Laraib; Aslam, Rakhshanda; Idrees, Umbreen; Habib, Fatima; Nasreen, Rizwana; Kanwal Malik, Iqra (Journal of Ayub Medical College Abbottabad, 2024)
Background: Membrane sweeping is a common obstetric intervention used to stimulate labor and decrease the duration of pregnancy. In spite of their widespread use, its efficacy in low-risk pregnancies remains debated. This research intended to evaluate effect of membrane sweeping on period of pregnancy in low-risk cases. Aim was to investigate the impact of membrane sweeping on duration of pregnancy in low-risk women. Methods: A prospective observational study was conducted from May 2023 to April 2024 involving 120 low-risk pregnant women. Participants were recruited from antenatal clinic of a tertiary care hospital. Inclusion criteria were singleton pregnancies between 38 and 40 weeks of gestation with no medical or obstetric complications. Participants were divided into two groups: the membrane sweeping group (n=60) and the control group (n=60). Membrane sweeping was performed during routine antenatal visits for the intervention group, while the control group received standard care without membrane sweeping. The primary outcome measured was the duration of pregnancy from the time of intervention to delivery. Secondary results included mode of delivery, incidence of spontaneous labor, and neonatal outcomes. Results: The mean duration of pregnancy from intervention to delivery was suggestively shorter in membrane sweeping group associated to control set (mean variance: 4.2 days, p<0.05). The incidence of spontaneous labor was higher in the membrane sweeping group (72%) related to control set (48%), and this variance was statistically substantial (p<0.05). There was no substantial variance in mode of delivery or neonatal outcomes among two sets. Conclusion: Membrane sweeping significantly reduced duration of pregnancy in low-risk cases and enlarged incidence of spontaneous labor without affecting mode of delivery or neonatal outcomes. These findings support the use of membrane sweeping as an effective intervention to expedite labor in low-risk pregnancies.